THE PROBLEM OF A JUST SOCIETY IN THE WORKS OF EASTERN SCIENTISTS - Islamov Kamol Toshqulovich (Scholar Express Journal, 2022)
The article gives a description of the Renaissance and Eastern scientists Muhammad ibn Musa al-Khwarizmi, Ahmed al-Farghani, Abu Nasr Farabi, Abu Raykhan Beruni, Abu Ali ibn Sina, Yusuf Khos Khadjib, Alisher Navai, Babur and in the works of many mystic scientists on science of Sufism, scientifically analyzed the rich spiritual heritage associated with the formation and management of a just society
Keywords: education; spirituality; natural-philosophical; religious